PENGARUH KREATIVITAS DAN KERJASAMA TIM TERHADAP KINERJA PENDAMPING UPPKH (UNIT PELAKSANA PROGRAM KELUARGA HARAPAN) KABUPATEN SAMPANG - Farid Alisyahbana; Iriani Ismail; RM Moch Wispandono (Trunojoyo University of Madura, 2015)
Creativity and teamwork were two urgents factors which can effect agent performance. Doing job, work agent often have problems, like is decrease creativity, giving fund agent un accurate, so become agent performance who optimal. The purposes this research are to know the effect of creativity and teamwork to agent performance, simultaneously and partially. This quantitative research used multiple linier regression analysis which 92 employees as sample using stratified sampling. Using this analysis, the results showed that creativity and teamwork effect positively 56,4 percent to agent performance simultaneously. Furthermore, the results showed that both influence to agent performance. Its shows that creativity provides 10,6 per cent to agent performance, while the teamwork provides 62,3 per cent to agent performace. Its means that teamwork provide dominant effect to agent performance.